2017
DOI: 10.1186/s12905-017-0422-y
|View full text |Cite
|
Sign up to set email alerts
|

Results of a pilot study in the U.S. and Vietnam to assess the utility and acceptability of a multi-level pregnancy test (MLPT) for home monitoring of hCG trends after assisted reproduction

Abstract: BackgroundTo evaluate the utility and acceptability of using multi-level pregnancy tests (MLPTs) at home to monitor hCG trends following assisted reproductive technology (ART).MethodsOne hundred and four women presenting for ART at either Stanford Medicine Fertility and Reproductive Health Clinic (Stanford, CA) or Hung Vuong Hospital (Ho Chi Minh City, Vietnam) participated in this pilot study. Women were asked to perform the MLPT at home, primarily on days when they were also scheduled to receive standard cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
(12 reference statements)
0
6
0
Order By: Relevance
“…The tests, PerioSafe and ImplantSafe, and reader (ORALyser) have been developed and manufactured by Medix Biochemica Ltd (Espoo, Finland) and dentognostics GmbH (Jena, Germany) and are commercially available from Dentognostics GmbH (Jena, Germany). In fact, the PoC/chair-side aMMP-8 lateral-flow immunotests resemble the classical pregnancy and/or recently described HIV-PoC tests [ 16 , 17 ]. The aMMP-8 oral fluid tests can be used according to the manufacturer's instructions [ 5 ].…”
Section: Periosafe and Implantsafe Ammp-8 Oral Fluid Poc/chair-simentioning
confidence: 82%
“…The tests, PerioSafe and ImplantSafe, and reader (ORALyser) have been developed and manufactured by Medix Biochemica Ltd (Espoo, Finland) and dentognostics GmbH (Jena, Germany) and are commercially available from Dentognostics GmbH (Jena, Germany). In fact, the PoC/chair-side aMMP-8 lateral-flow immunotests resemble the classical pregnancy and/or recently described HIV-PoC tests [ 16 , 17 ]. The aMMP-8 oral fluid tests can be used according to the manufacturer's instructions [ 5 ].…”
Section: Periosafe and Implantsafe Ammp-8 Oral Fluid Poc/chair-simentioning
confidence: 82%
“… 6 Home pregnancy tests have been shown to be an acceptable and feasible option for follow-up among couples undergoing assisted reproduction. 7 There is also evidence supporting the efficacy, safety and acceptability of urine pregnancy tests to confirm the effectiveness of a medical abortion instead of an ultrasound. 8 9 While urine pregnancy self-tests are available over-the-counter in many high-income and middle-income settings, in many low-income settings, they may be financially inaccessible to most people outside of public health services, or unavailable altogether, leading individuals with the sole option of health facility-based blood tests to confirm pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…In Madagascar, randomised trial data have shown that providing pregnancy tests to community health workers (CHWs) for home distribution can increase both engagement in antenatal care services5 and contraceptive services, since a negative pregnancy test is necessary before initiating some contraceptive methods 6. Home pregnancy tests have been shown to be an acceptable and feasible option for follow-up among couples undergoing assisted reproduction 7. There is also evidence supporting the efficacy, safety and acceptability of urine pregnancy tests to confirm the effectiveness of a medical abortion instead of an ultrasound 8 9.…”
Section: Introductionmentioning
confidence: 99%
“…Hormone monitoring is also used during early pregnancy to assess the developing fetus, offering the opportunity to intervene and prevent miscarriage [ 1 , 3 , 20 , 90 , 91 ], and could be of benefit to other areas of reproductive health. A pilot study assessed the use of a multi-level pregnancy test based on self-monitoring of urinary hCG trends after assisted reproduction [ 92 ]. The results found that 73% of women reported being ‘satisfied’ or ‘very satisfied’ with the home tests and 96.6% found it ‘easy’ or ‘very easy’ to use, and home test results were generally consistent with the results of clinic-based serum hCG testing [ 92 ].…”
Section: Telemedicine and Remote Treatment Monitoringmentioning
confidence: 99%
“…A pilot study assessed the use of a multi-level pregnancy test based on self-monitoring of urinary hCG trends after assisted reproduction [ 92 ]. The results found that 73% of women reported being ‘satisfied’ or ‘very satisfied’ with the home tests and 96.6% found it ‘easy’ or ‘very easy’ to use, and home test results were generally consistent with the results of clinic-based serum hCG testing [ 92 ]. Urinary hormone profiling has shown promise for studying corpus luteum deficiency, which may occur during early pregnancy as a result of insufficient progesterone levels.…”
Section: Telemedicine and Remote Treatment Monitoringmentioning
confidence: 99%